In Mandibular Second Molars, Prevalence of C-Shaped Root Canals - Mehmood Ahmed Rana, Anam Akram, Syed Abdul Rauf Shah, Mohammad Tahir, Saqlain Bin Syed Gilani, Khurram Nadeem (Pakistan Journal of Medical & Health Sciences, 2023)
Objective: The purpose of this study was to perform cone beam computed tomography (CBCT) to assess the frequency of mandibular second molars with C-shaped root canals in a population living in Pakistan. Study Design: Retrospective study Place and Duration: This retrospective study was conducted at Bakhtawar Amin Medical and Dental College during in the period from June, 2022 to November, 2022. Methods: Total 118 patients were presented with mandibular second molars scheduled for root canal treatment. CBCT scans of patients from diagnostic imaging center were selected. C-shaped root canals were determined by radiographic method using Fan’s criteria. The frequency and distribution of canals and their configuration along with the position of lingual/buccal grooves in the images were evaluated. SPSS 22.0 was used to analyze all data. Results: There were majority 72 (61.02%) females and 46 (38.98%) were males in this study. In our study mean age of the patients was 26.16±13.74 years. Frequency of C-shaped mandibular second molars was found in 12 (10.2%) cases. Among 12 cases, majority of the C-shaped root canals found in right side 7 (5.9%) and 5 (4.2%) C-shaped root canals found in left side. Majority of the C-shaped root canals found in females. Frequency of buccal groove among C-shaped root canals was 6 followed by both buccal and lingual groove in 4 and only lingual groove in 2 cases. Conclusion: According to CBCT analysis, 10.2% of second molars exhibited C-shaped canals. These teeth stood out due to the presence of a deep buccal groove. Right-sided mandibular second molar presence was statistically significant (P = 0.016), according to the data. Keywords: CBCT, Mandibular Second Molars, C-shaped canals, Buccal Groove